Antiretroviral Therapy Regimen Change Among HIV/AIDS Patients in Nekemt Hospital: a Primary Care Hospital in Oromia Regional State, Ethiopia - Meseret Wube, Andualem Tesfaye, Segewkal Hawaze (Journal of Applied Pharmaceutical Science, 2013)
ART brings a complex series of choices; when to initiate therapy, what regimen to use, which class of drugs to use, when to change therapy, and which alternative drugs to use. Therefore, this study aims to assess reasons for initial ART regimen change in Nekemt Hospital. A retrospective cross sectional study was done by reviewing patient information sheet recorded from January 1, 2006 to December 31, 2010. Patients who changed their regimen were included in the study to identify the reasons for change and descriptive statistics were generated using SPSS version 16. Out of 142 patients, 57.7% were females and 57.7% were inthe age group 20-34. 61.2% were WHO clinical stage III patients and 69.7% of patients had a CD4 count below 350 cells/mm3. The most common initial regimens were D4T/3TC/NVP (42.2%), D4T/3TC/EFV (27.5%) and AZT/3TC/EFV (12.7%). The main reasons for modification of therapy were toxicity (80.3%), pregnancy (6.3%), new TB (5.6%), stock out (4.9%) and treatment failure (2.8%). The main toxicity observed was lipoatrophy (58.8%) followed by rash (12.3%) and CNS toxicity (11.4%). Toxicity was the main reason for initial regimen modification. D4T based regimens had high incidence of lipoatrophy.
Keywords: Ethiopia, Adults, HAART, Toxicity and Lipoatrophy.&l